Islamic Law Analysis of Chemical Castration Punishments Post The Decision of Mojokerto State Court No. 69/PID.SUS/2019/PN MJK - Mgs M Hanief Fathurrahman; Muhammad Romli (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
This research aims to determine the judges' views and basis for deciding the castration chemical sentence in the Mojokerto District Court and to know the review of Islamic Law on the castration chemical decision in the Mojokerto District Court. The research is included in the category of qualitative research based on library research using secondary data sources and descriptive-analytical approaches. The data sources of this study were classified into three parts, namely, primary, secondary, and tertiary legal materials. In comparison, the data analysis in this study uses the deductive method. The conclusions of this research result explain that First, the Panel of judges gave a legal assessment of the Defendant that he had admitted his actions included the Act against the Law,